Slovenščina v Beneški Sloveniji in vloga dvojezične šole v Špetru pri medgeneracijskem prenosu jezika - Mezgec, Maja (Slovenščina 2.0, 2017)
The paper presents the first part of the study within the research project Opportunities and possibilities of preservation and revitalization of the Slovene language among the Slovene minority community in the neighbouring states, which aims to analyse the situation in Benečija. In the era of global processes, European integrational processes, more favourable and sound legal bases (protection laws) and especially because of bilingual schooling, we assume that in the province of Udine there are the premises for linguistic revitalisation and de-assimilation of younger generations, including the intergenerational transmission of language and/or study of Slovene among the generations where this transmission has been interrupted. The paper introduces the first results of the study which aims to analyse the intergenerational transmission of the Slovene language, the reasons why parents have chosen bilingual schools and their expectations about bilingual schooling. A combination of qualitative and quantitative data has been analysed. Available data concerning Slovenes in Italy has been reviewed. Special stress has been put on data regarding the areas of Udine/Videm and Benečija. In the empirical part, qualitative data has been collected with interviews among parents of children attending the bilingual school in the school year 2016/17. On the basis of the answers, it can be presumed that in the previous generation the intergenerational transmission of Slovene language was often interrupted as schooling started, more exactly nursery school, which marked the transition to Italian. Consequently, bilingual schooling represents an important achievement for the Slovene population of the province of Udine. However, bilingual schooling itself cannot guarantee language preservation and revitalisation. There is the need of more support by means of language planning and policies. It has to be highlighted that all these processes are going on in an environment that is increasingly open and favourable for the Slovene language and bilingualism.
Keywords: Slovene minority (Italy); zamejski Slovenci v Italiji; Beneška Slovenija (Italija); bilingual education; dvojezična vzgoja in izobraževanje; Slovenian language; slovenščina; de-assimilation; Slovene; intergenerational language transmission; jezikovna revitalizacija; deasimilacija; medgeneracijski prenos jezika